The TSC2 c.2742+5G>A variant causes variable splicing changes and clinical manifestations in a family with tuberous sclerosis complex - Fan, Kuan; Guo, Yi; Song, Zhi; Yuan, Lamei; Zheng, Wen; Hu, Xiao; Gong, Lina; Deng, Hao (Frontiers in Molecular Neuroscience, 2023)
Background Tuberous sclerosis complex (TSC) is a genetic, variably expressed, multisystem disease characterized by benign tumors. It is caused by pathogenic variants of the TSC complex subunit 1 gene (TSC1) and the TSC complex subunit 2 gene (TSC2). Genetic testing allows for early diagnosis, genetic counseling, and improved outcomes, but it did not identify a pathogenic variant in up to 25% of all TSC patients. This study aimed to identify the disease-causing variant in a Han-Chinese family with TSC. Methods A six-member, three-generation Han-Chinese family with TSC and three unrelated healthy women were recruited. A comprehensive medical examination, a 3-year follow-up, whole exome sequencing, Sanger sequencing, and segregation analysis were performed in the family. The splicing analysis results obtained from six in silico tools, minigene assay, and patients' lymphocyte messenger RNA were compared, and quantitative reverse transcription PCR was used to confirm the pathogenicity of the variant. Results Two affected family members had variable clinical manifestations including a rare bilateral cerebellar ataxia symptom. The 3-year follow-up results suggest the effects of a combined treatment of anti-epilepsy drugs and sirolimus for TSC-related epilepsy and cognitive deficits. Whole exome sequencing, Sanger sequencing, segregation analysis, splicing analysis, and quantitative reverse transcription PCR identified the TSC2 gene c.2742+5G>A variant as the genetic cause. This variant inactivated the donor splice site, a cryptic non-canonical splice site was used for different splicing changes in two affected subjects, and the resulting mutant messenger RNA may be degraded by nonsense-mediated decay. The defects of in silico tools and minigene assay in predicting cryptic splice sites were suggested. Conclusions This study identified a TSC2 c.2742+5G>A variant as the genetic cause of a Han-Chinese family with TSC and first confirmed its pathogenicity. These findings expand the phenotypic and genetic spectrum of TSC and may contribute to its diagnosis and treatment, as well as a better understanding of the splicing mechanism.